Jefferson's Memorandum Books, Volume 2 : Accounts, with Legal Records and Miscellany, 1767-1826 - Jefferson, Thomas, 1743-1826 (Princeton legacy library., 2018)
Among the Second Series of The Papers of Thomas Jefferson, this volume has the most detailed coverage of his day-to-day life. These disciplined records of personal expenditures, and of various other daily observations, furnish valuable information about prices and availability of commodities of the period and provide abundant evidence of Jefferson's devotion to a systematic way of living and of his insatiable curiosity.